Determination of critical speeds of planetary mill rotation - P. E. Vaytekhovich; A. V. Vavilov; G. M. Khvesko (Наука и техника)
Movement of grinding bodies in a planetary mill with external rolling of drums has been analyzed. The critical speeds of rotation characterizing operational regimes of a mill have been determined. Influence of design characteristics on value of critical speeds has been analyzed.